Water, Tourism, and Social Change: A Discussion of Environmental Perceptions in Bali - Thomas Wright (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
Water plays an important role in Balinese society. Not onlyis it commonly featured in Balinese Hindu rituals, butits use and management also enables prosperity through rice cultivation. While these aspects of water have beendiscussed in many academic and non-academic publications,qualitative understandings of relations to seawater remainsomewhat unexplored in the literature. The aim of this paperis to present a preliminary review of existing literature onwater and marine environments in Bali, and argue the needfor further qualitative social scientific understanding ofcontemporary Balinese relations to seawater. A discussionof existing research on ocean-centred communities andcontinued tourism development in Bali’s coastal areas isintended to add to current research in Balinese studies. Bypresenting literature on Balinese concepts of environment,water and the ocean, this paper seeks to highlight thebenefits of continued research on perceptions of environmentto discussions of pollution, water scarcity and resourcemanagement. Although maritime attractions such as thetemples at Tanah Lot and Uluwatu as well as several popularbeach communities play a significant role in the tourismindustry, this paper suggests the need to further investigatethe importance of these attractions to tourists and Balinese aswell as the social interpretations associated with them.